Effect of Endurance and Resistance Training on Parameters Related to Sexual Function in Men - AL Barari; AA Ayatollahi; S Shirali; M Ghasemi; A Hosseini; AR Ekrami; A Khandan Del (Medical Laboratory Journal, 2014)
Abstract Background and Objective: The hormonal responses are different, according to type, intensity and the duration of training. We aimed to compare the effect of endurance and resistance training in untrained men on the level sexual hormone including testosterone, estradiol, and on sex hormone binding globulin (SHBG). Material and Methods: this study was conducted on male Student Volunteers divided randomly into three groups of eight members, including endurance, resistance and control. To measure the variables, we performed sampling before and after the training program. Results: the levels of testosterone and estradiol, in both groups have a significant (p<0.05) increase and decrease respectively. SHBG level was significantly increased only in endurance group (p<0.05), But LH level was meaningfully increased only in the resistance group (p<0.05). Conclusion: The endurance and resistance training can increase the production of testosterone .Increased testosterone and decreased estradiol in men lead to sperm production and improve fertility. Keywords: Endurance training, Resistance Training, Testosterone, Estradiol